Welfare Is Not for Sale: Campaigns Against Welfare Profiteers in Milwaukee - Reese, Ellen (Social justice, 2006)
Part of a special issue on resistance to neoliberal globalization. In Milwaukee, Wisconsin, community and labor groups tried to oppose welfare privatization and enhance the delivery of welfare service. The labor and community activists drew media and government attention to the various scandals associated with privatization and lax supervision of welfare contractors and, in so doing, sought to mobilize popular opposition to welfare privatization and undermine its legitimacy. In addition, activists pressured welfare contractors into improving their services through disruptive protests, negative publicity, large public forums, and lobbying. Although activists could not convince Wisconsin politicians to return welfare administration to public civil servants, they succeeded in getting increased regulation of welfare contractors, a curbing of their worst abuses, and the termination of several welfare contracts.